2007
DOI: 10.1128/jvi.02497-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preexisting Immunity to Adenovirus Human Serotype 5 Antigens on the Immune Responses of Nonhuman Primates to Vaccine Regimens Based on Human- or Chimpanzee-Derived Adenovirus Vectors

Abstract: In this study we compared a prime-boost regimen with two serologically distinct replication-defective adenovirus (Ad) vectors derived from chimpanzee serotypes C68 and C1 expressing Gag, Pol, gp140, and Nef of human immunodeficiency virus type 1 with a regimen in which replication-defective Ad vectors of the human serotype 5 (AdHu5) were given twice. Experiments were conducted in rhesus macaques that had or had not been preexposed to antigens of AdHu5. There was no significant difference in T-cell responses te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
143
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 31 publications
4
143
2
Order By: Relevance
“…Human adenoviruses have been potent as gene-based vaccine vectors in mouse trials but have been less effective when scaled up to larger animals and humans (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Notably, most of these studies have used replication-defective Ad5 vectors, where E1 deletion renders the vector unable to amplify the one antigen gene that is delivered per viral genome to the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Human adenoviruses have been potent as gene-based vaccine vectors in mouse trials but have been less effective when scaled up to larger animals and humans (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Notably, most of these studies have used replication-defective Ad5 vectors, where E1 deletion renders the vector unable to amplify the one antigen gene that is delivered per viral genome to the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other poxvirus or adenovirus vectors (26,32,(61)(62)(63)(64), the ORFV vector allows repeated immunizations to enhance protective immunity against the transgene, which can be explained by the lack of serum antibodies efficiently neutralizing ORFV as well as by the generally shortliving ORFV immunity (38,40). Preexisting ORFV immunity in vaccine candidates is also highly unlikely due to the very restricted host range.…”
Section: Discussionmentioning
confidence: 99%
“…The preexisting immunity against AdV5 has been shown to reduce the vaccine efficacy (3,33,60). However, others observed that the preexisting immunity could be overcome by using larger amounts of vector or using alternate routes of administration (49,60).…”
Section: Discussionmentioning
confidence: 99%